Предмет: Алгебра,
автор: zvezdinakate4
помогите срочно пожалуйста дам 20 баллов
Приложения:
Ответы
Автор ответа:
1
Ответ:
В решении.
Объяснение:
15ab(16a² - b²) + 16ab(b² - 15a²) = при а = 10; b = -5;
= 15 * 10 * (-5) * (1600 - 25) + 16 * 10 * (-5) * (25 - 1500) =
= -750 * 1575 + (-800) * (-1475) =
= -1181250 + 1180000 = -1250.
Похожие вопросы
Предмет: Українська мова,
автор: lesyagrigorenk
Предмет: Русский язык,
автор: Аноним
Предмет: Окружающий мир,
автор: zakol66
Предмет: Математика,
автор: reshebnik45
Предмет: Обществознание,
автор: nastasia1234567890
15∗(10)(−5)+(16∗(10)2−(−5)2)+16∗(10)(−5)((−5)2−15∗(10)2) = 150